Reframing the Sliding Conductor Problem: Integrating Physical Principles and Pedagogical Scaffolding for Enhanced Conceptual Understanding - Zheng, Yubin (Journal of Research in Science and Engineering, 2026)
Conceptual understanding of physics is a core objective in science education. This study presents a systematic pedagogical analysis of a canonical electromagnetic system—a conducting bar sliding on rails in a uniform magnetic field—by examining both its intrinsic physical principles (knowledge logic) and the sequential reasoning and instructional scaffolding appropriate for learners (teaching logic). Through rigorous charge‑force analysis and coordinate transformation, the paper demonstrates that the Lorentz force performs no net work in this configuration, clarifying a widely misunderstood concept in classical electromagnetism. It further identifies the induced electromotive force expression ε = –dΦ/dt as a key conceptual bridge unifying electric and magnetic field representations. By translating these analytical insights into classroom practice, the study proposes a concrete implementation pathway that deepens students’ grasp of field‑circuit relationships and fosters transferable problem‑solving skills, ultimately contributing to the development of robust physical intuition in undergraduate physics education.